LOAD TRANSFER BEHAVIOUR OF BORED PILE IN TROPICAL SOILS AND ROCKS - HOE, ONG YIN (2021)
Performance based analysis of bored pile foundation has gained attention among engineers in Malaysia in solving the pile interaction problems with other structures. This requires an in-depth understanding of load transfer behaviour of bored pile. This research aimed to produce a model to estimate the pile bearing capacity and the pile settlement from large database.